A Cross-Cultural and Feminist Perspective on CSR in Developing Countries: Uncovering Latent Power Dynamics - Karam, Charlotte M. (Journal of business ethics, 2017)
In the current paper, our aim is to explore the latent power dynamics surrounding corporate social responsibility (CSR) in developing countries. To do this, we synthesize an analytic framework that borrows from both cross-cultural management literature (i.e., endogenous versus indigenous research) as well as feminist considerations of power (i.e., power over and power to). We then use the framework to examine three streams of CSR literature. Our analysis uncovers the prevalence of arguments and discussions about indigenous and power-over themes rather than more generative, endogenous, and power-to themes. The paper concludes with the suggestion for more space in the CSR literature for examining the realities and potentialities of local SME CSR expressions to counterbalance the overwhelming focus on MNCs. Such counterbalancing can better lead to the recognition that power and domination are not the only important dynamics to examine in CSR research. Just as important is the need for a more nuanced consideration of the role and contributions of different actors to the continuously unfolding CSR discourse.